Investigating the Relationship between the Use of ICT and Human Resource Empowerment in Iran Municipality (case study: Mazandaran Province) - Ahmadi, Masoud; Sharifi Asadi Malafe, Neda; Baei, Fahime (International Journal of Engineering and Technology, 2018)
This Research was a push to look into the association amongst information and correspondence innovation (ICT) and its parts with authorisation of Mazandaran region specialists as administrative organizations. "Research Philosophy" amid this examination was distinct and correspondence. to fulfill the point of this examination, 152 laborers were hand-picked from among a total scope of 250 populace upheld agent inspecting abuse Krejcie and Morgan testing table. "The data assortmenttools" comprised of 2 standard surveys, and in addition ICT shapes (%96 legitimacy) and authorisation poll eighty sevenvalidity). "The data examination technique" was inferential measurements leading by SPSS and LISREL code. "The outcomes" demonstrated that there was a major connection amongst ICT and authorisation. Additionally, that there was a major connection between ICT parts include: "robotization", "preparing", "capacity", "advising" and "correspondence", and authorisation. On the contrary hand, the connection amongst ICT and authorisation by statistic qualities partition demonstrated that there's a major connected math distinctionwithin the level of relationship amongst's ICT and authorisation in a few instructional groups, anyway there's not a major connected math refinement inside the level of connection between's 2 groups of sexual orientation and 3 groups of work skill. At long last, the association amongst ICT and information administration demonstrate upheld work Files of, appropriately assessed.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â